Trends in Treatment of T1N0 Esophageal Cancer - Semenkovich, Tara R. (Ann Surg, 2019)
OBJECTIVE: The purpose of this study was to explore nationwide trends in treatment and outcomes of T1N0 esophageal cancer. BACKGROUND: Endoscopic treatment has become an accepted option for early-stage esophageal cancer, but nationwide utilization rates and outcomes are unknown. METHODS: T1N0 esophageal cancers were identified in the National Cancer Database from 2004 to 2014. We assessed trends in treatment; compared endoscopic therapy, esophagectomy, chemoradiation, and no treatment; and performed a subgroup analysis of T1a and T1b patients from 2010 to 2014 (AJCC 7). RESULTS: A total of 12,383 patients with clinical T1N0 esophageal cancer were analyzed. Over a decade, use of endoscopic therapy increased from 12.7% to 33.6%, whereas chemoradiation and esophagectomy decreased, P <0.01. The rise in endoscopic treatment of T1a disease from 42.7% to 50.6% was accompanied by a decrease in esophagectomies from 21.7% to 12.8% (P < 0.01). For T1b disease, the rise in endoscopic treatment from 16.9% to 25.1% (P = 0.03) was accompanied by decreases in no treatment and chemoradiation, whereas the rate of esophagectomies remained approximately 50%. Unadjusted median survival was longer for patients undergoing resection: esophagectomy, 98.6 months; endoscopic therapy, 77.7 months; chemoradiation, 17.3 months; no treatment, 8.2 months; P < 0.01. Riskadjusted Cox modeling showed esophagectomy was associated with improved survival [hazard ratio (HR): 0.85], and chemoradiation (HR: 1.79) and no treatment (HR: 3.57) with decreased survival, compared to endoscopic therapy (P < 0.01). CONCLUSIONS: Use of endoscopic therapy for T1 esophageal cancer has increased significantly: for T1a, as an alternative to esophagectomy; and for T1b, as an alternative to no treatment or chemoradiation. Despite upfront risks, long-term survival is highest for patients who can undergo esophagectomy.